Development of two shortened systematic review formats for clinicians - Perrier, Laure; Persaud, Nav; Ko, Anita; Kastner, Monika; Grimshaw, Jeremy; McKibbon, K A; Straus, Sharon E (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Systematic reviews provide evidence for clinical questions, however the literature suggests they are not used regularly by physicians for decision-making. A shortened systematic review format is proposed as one possible solution to address barriers, such as lack of time, experienced by busy clinicians. The purpose of this paper is to describe the development process of two shortened formats for a systematic review intended for use by primary care physicians as an information tool for clinical decision-making. Methods We developed prototypes for two formats (case-based and evidence-expertise) that represent a summary of a full-length systematic review before seeking input from end-users. The process was composed of the following four phases: 1) selection of a systematic review and creation of initial prototypes that represent a shortened version of the systematic review; 2) a mapping exercise to identify obstacles described by clinicians in using clinical evidence in decision-making; 3) a heuristic evaluation (a usability inspection method); and 4) a review of the clinical content in the prototypes. Results After the initial prototypes were created (Phase 1), the mapping exercise (Phase 2) identified components that prompted modifications. Similarly, the heuristic evaluation and the clinical content review (Phase 3 and Phase 4) uncovered necessary changes. Revisions were made to the prototypes based on the results. Conclusions Documentation of the processes for developing products or tools provides essential information about how they are tailored for the intended user. One step has been described that we hope will increase usability and uptake of these documents to end-users.